America's working women: A documentary history, 1600 to the present - Baxandall, Rosalyn Fraad, (1939- ...).; Gordon, Linda; Reverby, Susan (W.W. Norton, 1995)
A landmark work when it appeared in 1976, America's Working Women helped form the field of women's studies and transform labor history. Now the authors have enlarged the dimensions of this important anthology; more than half the selections and all the introductory material are new. Spanning the years from 1600 to the present, selections from diaries, popular magazines, historical works, oral histories, letters, songs, poetry, and fiction show women's creativity in supporting themselves, their families, and organizations or associations. Slave women recall their field work, family work, and sabotage. We see Indian women farming, and we also see the white culture coercing Indian women to give up farming. We see women in industry playing a central part in the union movement while facing the particular hazards of women's jobs and working conditions. New selections show the historical origins of today's important issues: sexual harassment, equal pay, "sex work," work in the underground economy, work in the home, and shift work. With an expanded focus on women from all racial and ethnic backgrounds and regions, America's Working Women grounds us in the battles women have fought and the ones they are in the process of winning.
Keywords: 1600-1699; 1700-1799; 1800-1899; 1900-1999; amériques; approches et analyses; cours; discipline; discours dominant; droits des femmes*; famille; his4443; histoire; histoire des femmes*; histoire et politique; inégalités; premier cycle; périodes historiques; racisme; racisme systémique; rapports sociaux de sexe; régions géographiques; sciences humaines; système colonial; systèmes d'oppressions; thématiques; travail; travail des femmes*; états-unis

Moi, Tituba sorcière --: noire de Salem - Condé, Maryse; De Serres, Murielle; Thérien, Michel; Jean, Julie (Littératures et cultures, 1995)
Fille d'une esclave violée par un marin anglais à bord d'un vaisseau négrier, Tituba, née à la Barbade, est initiée aux pouvoirs surnaturels par Man Yaya, guérisseuse et faiseuse de sorts. Son mariage avec John Indien l'entraîne à Boston puis au village de Salem, au service du révérend Samuel Parris. Elle est emprisonnée à la suite du procès des sorcières de Salem en 1692.
Keywords: afro-féminisme; amériques; approches et analyses; arts; barbade; caraïbes; cours; discipline; féminismes noirs; histoire et politique; lit2815; premier cycle; roman; régions géographiques; système colonial; systèmes d'oppressions; thématiques; états-unis; études littéraires

Killing rage: ending racism - hooks, bell (Penguing Books, 1995)
"One of our country's premier cultural and social critics, bell hooks has always maintained that eradicating racism and eradicating sexism must go hand in hand. But whereas many women have been recognized for their writing on gender politics, the female voice has been all but locked out of the public discourse on race. Killing Rage speaks to this imbalance. These twenty-three essays are written from a black and feminist perspective, and they tackle the bitter difficulties of racism by envisioning a world without it"--Back cover.
Keywords: afro-féminisme; amériques; approches et analyses; féminismes noirs; justice sociale; racisme; régions géographiques; sexisme; systèmes d'oppressions; états-unis

Thunder in my soul: a Mohawk woman speaks - Monture-Angus, Patricia (Fernwood Publishing, 1995)
"This book contains the reflections of one Mohawk woman and her struggles to find a good place to be in Canadian society. The essays, written in enjoyable and accessible language, document the struggles against oppression that Aboriginal people face, as well as the success and change that have come to Aboriginal communities. It speaks to both the mind and the heart."--Résumé de l'éditeur.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; amériques; approches et analyses; canada; cours; discipline; féminisme autochtone; histoire et politique; inégalités; mohawk; pol4105; premier cycle; périodes historiques; régions géographiques; science politique; science politique et droit; sciences de l'éducation; système colonial; systèmes d'oppressions; thématiques

Identités en devenir et famille subvertie dans l'oeuvre de Jovette Marchessault - Poirier, Martin (Université du Québec à Montréal, 1995)
Ce mémoire présente une analyse du roman Des cailloux blancs pour les forêts obscures (Montréal: Leméac, 1987) de Jovette Marchessault. L'approche théorique utilisée est avant tout inspirée du travail de Marianne Hirsch (The Mother/Daughter Plot, 1989) qui revoit la notion de «roman familial» de Freud d'un point de vue féministe. Les réflexions de Luce Irigaray et de Claire Lejeune à propos de la notion identitaire et de la constitution de famille servent également à l'analyse. La question principale qui guide l'ensemble des quatre chapitres du mémoire est la suivante: en quoi les remises en question identitaires des personnages féminins et masculins arrivent-elles à transformer les structures de la famille patriarcale et les caractéristiques du roman familial traditionnel?
Keywords: amériques; approches et analyses; arts; discipline; famille; mémoires/thèses; patriarcat; québec; régions géographiques; systèmes d'oppressions; thématiques; études littéraires

Of woman born: Motherhood as experience and institution - Rich, Adrienne (Norton, 1995)
Adrienne Rich's influential and landmark investigation concerns both the experience and the institution of motherhood. The experience is her own—as a woman, a poet, a feminist, and a mother—but it is an experience determined by the institution, imposed on all women everywhere. She draws on personal materials, history, research, and literature to create a document of universal importance. Dans Of Woman Born , initialement publié en 1976, la poétesse et féministe influente Adrienne Rich examine les systèmes patriarcaux et les institutions politiques qui définissent la maternité. En explorant sa propre expérience - en tant que femme, poète, féministe et mère - elle trouve que l'acte de materner est à la fois déterminé par et distinct de l'institution de la maternité telle qu'elle est imposée à toutes les femmes partout dans le monde
Keywords: 1900-1999; 1970-1979; amériques; approches et analyses; corps; cours; discours dominant; fem1000; maternité; premier cycle; périodes historiques; régions géographiques; santé; systèmes d'oppressions; thématiques; théories féministes; états-unis

Bisexuality and the challenge to lesbian politics: Sex, loyalty, and revolution. - Rust, Paula C. (The Cutting Edge: Lesbian Life and Literature Series, 1995)
Le sujet de la bisexualité continue de diviser la communauté lesbienne et gay. Lors des marches des fiertés, dans des films comme Go Fish, lors de conférences universitaires, le rôle et le statut des bisexuels sont âprement contestés. Au sein des communautés lesbiennes, constituées pour soutenir les lesbiennes dans une société patriarcale et hétérosexiste, les femmes bisexuelles sont souvent perçues comme une menace ou comme une faiblesse politique. Les femmes bisexuelles se sentent considérées avec suspicion et méfiance, voire ouvertement méprisées. S'appuyant sur ses recherches auprès de plus de 400 femmes bisexuelles et lesbiennes, sur le traitement de la bisexualité dans la presse lesbienne et gay et sur la croissance récente d'un mouvement bisexuel résolument politique, Paula Rust aborde une série de questions relatives à la politique et relations sociales entre lesbiennes et femmes bisexuelles. En remontant les racines de la controverse sur la bisexualité parmi les lesbiennes aux premiers débats féministes lesbiens des années 1970, Rust soutient que ces débats ont créé les circonstances dans lesquelles la bisexualité est devenue un défi inévitable à la politique lesbienne. Elle le retrace également, prédisant l’avenir de la politique sexuelle.
Keywords: amériques; approches et analyses; bisexualité; discours dominant; histoire et politique; hétérosexisme; identités LGBTQIA2+; lesbianisme; militance; ressource en ligne; régions géographiques; sexualité; systèmes d'oppressions; thématiques; états-unis